Stories and Problem Solving in Mathematics: a path to the development of children's creative thinking in Preschool - Kraft, Ana Luiza Candido; Silva, Viviane Clotilde da (Educação Matemática Debate, 2025)
The research analyzed the development of creative thinking and the understanding of mathematical notions through practices that explore solving mathematical problems related to a children's story. The study is part of a qualitative research of the action-research type; presents discussions on creativity and the use of children's stories and problem-solving for its development. It also describes and analyzes a practice carried out with children in Prescchool. The data collection instruments used were: the records of the teacher-researcher and the children, as well as images. The analyses indicated that activities of this type stimulate children to seek out different strategies and resolutions, characteristics of creative thinking, and allow them to internalize the mathematical notions explored.